HUBUNGAN PENGETAHUAN DAN PERSEPSI PUS PRIA DENGAN PENGGUNAAN KONDOM /VASEKTOMI DI KELURAHAN MERDEKA WILAYAH PUSKESMAS KUPANG KOTA - Meri Flora Ernestin (CHMK MIDWIFERY SCIENTIFIC JOURNAL, 2019)
Male participation in family planning and reproductive health is male responsibility, family planning involvement and participation, aimed at controlling births, and helping families and individuals to realize their reproductive rights through health services, regulating the number of children and supporting families with an ideal age of marriage and the ideal age for giving birth. The participation of PUS men with condom use and vasectomy is very low in the Solor sub-district of the Kupang Kota health center area. Preliminary research on the number of couples of reproductive age 310, who were active family planning participants, 165 participants who were dominated by women namely (52.0%), male active family planning participants used condoms and vasectomy (1.29%). The purpose of analyzing the relationship of knowledge and perceptions of male PUS is to use condoms and vasectomy. Method: Analytical survey study with cross sectional design on 111 male PUS in Solor Village Kupang Kota Puskesmas area. Results Bivariate analysis with the chi square test found that there was a relationship between the two independent variables on the dependent variable (Knowledge level p. Value 0.0001 < = 0.05; Perception p value 0.005 < = 0.05; the calculated significance is smaller than the significance level of the table. The conclusion is that there is a relationship between knowledge, perception, and condom use and vasectomy. Keywords: Participation in EFA, Condoms, Vasectomy